ادارة الخدمات اللوجستية في نشاط البيع بالجملة - مولاي, عمر (My University, 2024)
Logistics services play an important role in supporting distribution activity in general and wholesale activity in particular, through logistical activities represented in transportation, storage and other activities, which in turn represent the link between all the active elements in delivering the product efficiently from the place of its production to the place of its consumption, where the logistics department coordinates Between these various activities to achieve operational efficiency. Effective management of logistics services aims to achieve competitive advantage by achieving temporal and spatial benefit, which leads to reducing costs and achieving customer requirements through rapid response to him and thus gaining his satisfaction
ABC DISTRIBUTION دراسة حالة